Burnout in the service mobile pre-hospital: perception of nurses - Claudia Cristiane Filgueira Martins; Andrezza Graziella Veríssimo Pontes; Alcivan Nunes Viera; Viviane Euzébia Pereira Santos (Universidade Federal de Santa Maria, 2012)
Objective: to describe how nurses in pre-hospital care perceived work-related burnout. Method: qualitative descriptive study, conducted through interviews with seven nurses of the emergency mobile service (SAMU) Mossoró, Brazil. The data collection period was from March to April 2010 and data were analyzed in the light of discourse analysis (DA). Results: the data were treated in the light of discourse analysis (DA) and classified in three clusters of meaning: wear related to the peculiarities of the pre-hospital care; wear and conditions of service and wear related to the physical body and mind. Conclusions: with the completion of this study perceive that nurses understand that work-related wear is exacerbated by working conditions and working hours of these professionals